Development and validation of a tool to assess underlying factors of iron‐rich food consumption among pregnant women - Sall Mohamadou; Ndiaye Ndene Aminata; Dupuis Jérémie Bobby; Ba Lo Nafissatou; Thiam El Hadj Momar; Blaney Sonia (Maternal and Child Nutrition)
Abstract Anaemia among pregnant women remains a public health concern globally. One major cause of this persistent problem is iron deficiency, which may be the result of limited iron intake in the diet. Using the extended version of the theory of planned behaviour (eTPB), this study aims to develop and validate a questionnaire assessing psychosocial and environmental factors that could influence the consumption of iron‐rich foods (IRFs) among Senegalese pregnant women. A three‐step procedure was used. Six focus group discussions (FGDs) were held with 10 pregnant women each from a different region to identify salient beliefs related to each of the four constructs of the eTPB using a structured guide. Information from FGDs was used to develop a questionnaire, which was administered to the first group (n = 200) of pregnant women. Principal component analyses and exploratory factorial analyses were performed on the first set of data to identify latent factors for each construct namely the attitude, subjective norm and perceived behavioural control. A revised and shorter version of the questionnaire was administered to a second sample of pregnant women (n = 226) and confirmatory factorial analyses were conducted using this second set of data. Hancock and Muller's H reliability index was computed on the final model. The final questionnaire included 44 items. Most criteria for fit indices were met and H values were satisfactory. This study proposes a tool that could be used to explore determinants of the consumption of IRF among pregnant women. Further validation is still warranted in other contexts.